2017
DOI: 10.1017/pab.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

Dietary responses of Sahul (Pleistocene Australia–New Guinea) megafauna to climate and environmental change

Abstract: Abstract.-Throughout the late Quaternary, the Sahul (Pleistocene Australia-New Guinea) vertebrate fauna was dominated by a diversity of large mammals, birds, and reptiles, commonly referred to as megafauna. Since ca. 450-400 Ka, approximately 88 species disappeared in Sahul, including kangaroos exceeding 200 kg in size, wombat-like animals the size of hippopotamuses, flightless birds, and giant monitor lizards that were likely venomous. Ongoing debates over the primary cause of these extinctions have typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 80 publications
(208 reference statements)
3
53
0
Order By: Relevance
“…between certain distantly related taxa), but to document differences in diet when they might not necessarily be expected based on tooth morphology alone. Differences between closely related taxa have been captured, for instance, in bovids (Scott, 2012; Ungar, Merceron, & Scott, 2007), cervids (Berlioz, Kostopoulos, Blondel, & Merceron, 2017), ungulates (Schulz, Calandra, & Kaiser, 2010), feliforms (DeSantis & Haupt, 2014; DeSantis, Tseng, et al, 2017), canids (DeSantis et al, 2015), primates (Scott et al, 2005; Ungar, Grine, & Teaford, 2008), and macropodids (DeSantis, Field, Wroe, & Dodson, 2017; Prideaux et al, 2009). Indeed, many bioarchaeological studies have demonstrated distinctive and predictable diet‐related differences in both gross dental wear and microwear within a single species, Homo sapiens (Rose & Ungar, 1998).…”
mentioning
confidence: 99%
“…between certain distantly related taxa), but to document differences in diet when they might not necessarily be expected based on tooth morphology alone. Differences between closely related taxa have been captured, for instance, in bovids (Scott, 2012; Ungar, Merceron, & Scott, 2007), cervids (Berlioz, Kostopoulos, Blondel, & Merceron, 2017), ungulates (Schulz, Calandra, & Kaiser, 2010), feliforms (DeSantis & Haupt, 2014; DeSantis, Tseng, et al, 2017), canids (DeSantis et al, 2015), primates (Scott et al, 2005; Ungar, Grine, & Teaford, 2008), and macropodids (DeSantis, Field, Wroe, & Dodson, 2017; Prideaux et al, 2009). Indeed, many bioarchaeological studies have demonstrated distinctive and predictable diet‐related differences in both gross dental wear and microwear within a single species, Homo sapiens (Rose & Ungar, 1998).…”
mentioning
confidence: 99%
“…The microfossil record and the sediment facies of fine clay with little silt (Field and Dodson, ) indicates a lacustrine and non‐fluvial setting, an interpretation confirmed by electromagnetic survey (see Field et al ., ). Discrepancies in dating studies, interpreted by some researchers as indicating site disturbance, have no support in the systematically compiled site data investigating the geomorphology, archaeology and fossil faunal sequences (see discussion in Field and Wroe, ; DeSantis et al ., ). Notably, contrary to the unsupported assertions of Grün et al .…”
Section: Discussionmentioning
confidence: 89%
“…The lower (SU9) and upper (SU6A, SU6B) layers have several megafauna taxa in common although the species diversity appears to have contracted significantly by the time SU6A/B formed (Fillios et al ., ; see also DeSantis et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations